2010
DOI: 10.1073/pnas.1000324107
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet A does not induce melanomas in a Xiphophorus hybrid fish model

Abstract: We examined the wavelength dependence of ultraviolet (UV) radiation (UVR)-induced melanoma in a Xiphophorus backcross hybrid model previously reported to be susceptible to melanoma induction by ultraviolet A (UVA) and visible light. Whereas ultraviolet B (UVB) irradiation of neonates yielded high frequencies of melanomas in pigmented fish, UVA irradiation resulted in melanoma frequencies that were not significantly different from unirradiated fish. Spontaneous and UV-induced melanoma frequencies correlated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 36 publications
3
69
0
Order By: Relevance
“…Thus, studies performed on animals (opossum, 4 fish, 5 mice 6 ) suggest that it provokes the formation of papillomas, squamous cell 35 carcinomas (SCC) and melanomas; however, the role played by UVA-mediated oxidative damage to DNA in melanoma induction, using xiphophorus fishes as model, has been recently questioned. 5,7 While UVB is efficiently absorbed by the nucleobases, 40 causing direct photoreactions of DNA, UVA-induced damage is commonly the result of photosensitisation. Thus, modifications in DNA may occur after light absorption by endogenous or exogenous chromophores present in drugs, cosmetic agents, metabolites, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, studies performed on animals (opossum, 4 fish, 5 mice 6 ) suggest that it provokes the formation of papillomas, squamous cell 35 carcinomas (SCC) and melanomas; however, the role played by UVA-mediated oxidative damage to DNA in melanoma induction, using xiphophorus fishes as model, has been recently questioned. 5,7 While UVB is efficiently absorbed by the nucleobases, 40 causing direct photoreactions of DNA, UVA-induced damage is commonly the result of photosensitisation. Thus, modifications in DNA may occur after light absorption by endogenous or exogenous chromophores present in drugs, cosmetic agents, metabolites, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in these fish however showed that visible and UVA radiation, as well as UVB (Setlow et al, 1993) induced lesions, which raised concern that UVA might be causal for human melanoma as well or instead of UVB. However this could not be confirmed in later experiments (Mitchell et al, 2010). A mammalian opossum model also developed melanoma-like lesions after broadband UVA exposure but with low potency compared to broad-band UVB (Robinson et al, 2000).…”
Section: Experimental Animal Studiesmentioning
confidence: 78%
“…Recently Timmins and colleagues used electron paramagnetic resonance assays to show that the action spectrum for melanoma and melanin radical production overlap (Wood et al, 2006), further evidence for melanin radical causation. However the notion that UVA is more effective than UVB in inducing melanoma in fish has been questioned by Mitchell et al, (2010), after similar experiments using apparently the same strain of fish. This conflicting result from the original study (Setlow et al, 1989) may be largely explained by the fact that latest study used more animals to make the results more statistically significant, and followed the fish for a longer time, allowing for later age of onset of some melanomas.…”
Section: Evidence Of Uva Causality In Melanomamentioning
confidence: 99%